Chewing Gum on Reducing Thirst in Chronic Kidney Disease Patients Undergoing Hemodialysis - Putro, Dimas Utomo Hanggoro; Asri, Nurainah Fajriati Sagita; Yulinar, Yulinar (Jurnal Keperawatan Profesional (KEPO), 2025)
Restrictions on fluid intake that must be carried out in patients with chronic kidney failure can cause thirst and dry mouth. This study aimed to determine the effect of chewing gum on thirst in patients with chronic kidney failure undergoing hemodialysis. The method used was a literature review with the Google Scholar database. The keywords used were "Chronic Kidney Disease Patient AND Chewing Gum AND Reducing Thirst AND Hemodialysis". Inclusion criteria included full-text articles from 2021-2024 in Indonesian or English published from national or international journals. The types of articles are Randomized Controlled Trial (RCT), quasi-experimental, and case studies. Fifteen articles met the inclusion criteria. The conclusion was that chewing gum can reduce thirst in patients with chronic kidney failure undergoing hemodialysis.